Physical and Chemical Properties on Reduction Behaviour of Chromium Doped to Molybdenum Oxide in Carbon Monoxide Environment - Nur Syakirah Abdul Rahim; Alinda Samsuri; Mohd Nor Latif; Maratun Najiha Abu Tahari; Fairous Salleh; Tengku Shafazila Tengku Saharuddin; Norliza Dzakaria; Muhammad Rahimi Yusop (Malaysian Analytical Sciences Society (ANALIS), 2024)
Vol 27 No 2